Analysis of the Kurikulum Merdeka on plane figures: A case study of elementary school students - Alma Dina Dwi Marlina; Harinaredi Harinaredi (Universitas Pendidikan Indonesia, 2025)
The implementation of the Kurikulum Merdeka in mathematics education. This study aims to provide opportunities to apply a contextual approach grounded in the surrounding environment. This study highlights the use of concrete objects, such as bottle caps, pencil boxes, and folded paper, as learning media that help students understand geometric concepts more tangibly. Using a case study method, data were collected through observation, interviews, and documentation of a teacher and three fourth-grade students. The results show that this approach not only strengthens students' understanding but also increases their active involvement in the learning process. Teachers have the flexibility to design creative learning strategies tailored to students' needs. However, constraints such as limited time and students' readiness to bring learning materials from home remained. Evaluation was conducted both formatively and reflectively, focusing on the exploration process and concept understanding. Therefore, improved teacher training and support from parents and school authorities are needed to strengthen the implementation of contextual learning. Overall, this approach is considered effective in creating a fun, relevant, and meaningful mathematics learning environment for elementary school students. Abstrak Penerapan Kurikulum Merdeka dalam pembelajaran Matematika, khususnya materi bangun datar di sekolah dasar. Penelitian ini bertujuan untuk memberikan peluang dalam menerapkan pendekatan kontekstual berbasis lingkungan sekitar. Studi ini menyoroti penggunaan benda konkret seperti tutup botol, kotak pensil, dan kertas lipat sebagai media pembelajaran yang dapat membantu murid memahami konsep geometri secara lebih nyata. Menggunakan metode studi kasus, data dikumpulkan melalui observasi, wawancara, dan dokumentasi terhadap seorang guru dan tiga murid kelas IV. Hasilnya menunjukkan bahwa pendekatan ini tidak hanya memperkuat pemahaman murid, tetapi juga meningkatkan keterlibatan aktif mereka dalam proses belajar. Guru memiliki keleluasaan dalam merancang strategi pembelajaran yang kreatif dan sesuai kebutuhan murid. Meskipun demikian, kendala seperti terbatasnya waktu dan kesiapan murid dalam membawa media pembelajaran dari rumah masih ditemukan. Evaluasi dilakukan secara formatif dan reflektif, dengan fokus pada proses eksplorasi dan pemahaman konsep. Oleh karena itu, peningkatan pelatihan guru dan dukungan dari orang tua serta pihak sekolah diperlukan untuk memperkuat pelaksanaan pembelajaran kontekstual. Secara keseluruhan, pendekatan ini dinilai efektif dalam menciptakan suasana belajar Matematika yang menyenangkan, relevan, dan bermakna bagi murid sekolah dasar Kata Kunci: bangun datar; kurikulum merdeka; pembelajaran konseptual